2020
DOI: 10.1161/circresaha.120.316655
|View full text |Cite
|
Sign up to set email alerts
|

CD84 Links T Cell and Platelet Activity in Cerebral Thrombo-Inflammation in Acute Stroke

Abstract: Rationale: Ischemic stroke is a leading cause of morbidity and mortality worldwide. Recanalization of the occluded vessel is essential but not sufficient to guarantee brain salvage. Experimental and clinical data suggest that infarcts often develop further due to a thromboinflammatory process critically involving platelets and T cells, but the underlying mechanisms are unknown. Objective: We aimed to determine the role of CD (cluster of differentiation)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 50 publications
(79 reference statements)
2
51
0
Order By: Relevance
“…Blocking either GPIb or its ligand VWF A1 domain with an antibody, or their genetic deletion, significantly reduced the number of infiltrated T cells and infarct volume (92)(93)(94). Another platelet-born pro-infiltration factor is CD84, a soluble homophilic immunoreceptor that is shed from platelets after ischemic stroke (70). It binds to CD84 on T cells and enhances CD4+ lymphocyte migration in vitro (70).…”
Section: Thrombo-inflammationmentioning
confidence: 99%
See 1 more Smart Citation
“…Blocking either GPIb or its ligand VWF A1 domain with an antibody, or their genetic deletion, significantly reduced the number of infiltrated T cells and infarct volume (92)(93)(94). Another platelet-born pro-infiltration factor is CD84, a soluble homophilic immunoreceptor that is shed from platelets after ischemic stroke (70). It binds to CD84 on T cells and enhances CD4+ lymphocyte migration in vitro (70).…”
Section: Thrombo-inflammationmentioning
confidence: 99%
“…Another platelet-born pro-infiltration factor is CD84, a soluble homophilic immunoreceptor that is shed from platelets after ischemic stroke (70). It binds to CD84 on T cells and enhances CD4+ lymphocyte migration in vitro (70). Mice deficient in platelet or T cell CD84 developed smaller infarct volumes and had fewer infiltrated T cells (70).…”
Section: Thrombo-inflammationmentioning
confidence: 99%
“…Numerous studies have demonstrated that neuroinflammatory response plays an essential role in the pathophysiology of ischemic stroke [ 11 14 ]. Neutrophil to lymphocyte ratio (NLR), platelet to lymphocyte ratio (PLR), and lymphocyte to monocyte ratio (LMR) have recently been reported as potential novel biomarkers of baseline inflammatory process and could serve as outstanding predictors in patients with ischemic stroke [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Again, the beneficial effect was not associated with an increased risk of bleeding. Recent studies in mouse models of stroke have provided further evidence for T-cell interactions with platelets [ 144 ].…”
Section: Role Of Thromboinflammation In Asahmentioning
confidence: 99%